Pelatihan Keamanan Akun Digital sebagai Upaya Preventif Gangguan Mental pada Siswa SMK Yadika 13 - Simorangkir, Melda Rumia Rosemary (CV. Dalle’ Deceng Abeeayla, 2025)
In the context of vocational secondary education, digital literacy and account security have become crucial aspects that demand serious attention. As digital natives, vocational high school students are vulnerable to various cyber threats, including data breaches, identity misuse, and cyberbullying, all of which can negatively impact their mental health. This Community Service Program was designed as a concrete response to these issues through a digital account security training conducted at SMK Yadika 13 Tambun. The program targeted all 11th and 12th-grade students, aiming to equip them with knowledge and preventive skills to safeguard their digital identities responsibly and ethically. The implementation involved material presentation, interactive discussions, and simulations facilitated by lecturers and students from various study programs at the Christian University of Indonesia. The training resulted in high levels of participant enthusiasm, an educational and inclusive atmosphere, and the emergence of initial awareness about the importance of digital security. This activity is expected to be replicated in more schools as part of a collective effort to create a digital ecosystem that is safe, mentally healthy, and supportive of the holistic development of Indonesia’s younger generation.